Relationship between Determinants of E-Waste Recycling and E-Waste Recycling Intention among Gen Y in Malacca - Koh, Qi Herng; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2026)
Electronic waste(e-waste) has become a growing environmental concern in Malaysia due to rapid technological advancement and increased consumption of electronic device. Generation Y (Gen Y) as active users of electronic products play an important role in promoting sustainable e-waste management practices. This study aims to examine the relationship between determinants of e-waste recycling and e-waste recycling intention among Gen Y in Malacca by applying the Theory of Planned Behavior (TPB), focus on attitude, subjective norms and perceived behavioral control. A quantitative approach was employed using an online questionnaire and data were collected from 207 Gen Y respondents residing in Malacca. The data were analyzed using SPSS through descriptive analysis, reliability analysis, normality analysis and Spearman’s correlation analysis. The findings indicate that attitude, subjective norms, perceived behavioral control and e-waste recycling intention are all at a high mean level. In addition, the result reveals that attitude, subjective norms and perceived behavioral control have significant and positive relationships with e-waste recycling intention. These findings support the applicability of the TPB in explaining e-waste recycling intentions and provide useful insights for policymakers and environmental agencies to enhance e-waste recycling initiatives among Gen Y in Malacca.